Epidemiology of injuries in judo: a cross-sectional survey of severe injuries based on time loss and reduction in sporting level - Akoto, R.; Lambert, C.; Balke, M.; Bouillon, B.; Frosch, K.-H.; Höher, J. (British Journal of Sports Medicine, 2018)
Background: Sport injury severity can be detected by duration of time loss and reduction of sporting performance.